Health Beliefs Related to Breast Cancer and Breast Self- Examination among Indian Women: Effect of Educational Program - Apoorva Dev.M; Githa Kishore; Faezeh khodadadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Breast cancer is believed to be the most widespread carcinoma all over the world and themost frequent type of carcinoma among females in India. Approximately 40% of breast lesions which leadto breast cancer is detectable by breast self-examination (BSE). The identification of the barriers of earlydetection and the baseline knowledge on breast cancer symptoms, risk factors, BSE method and also theeffectiveness of a health education intervention among females in Bangalore, India are the main purposesof this research.Methodology: The study was composed of totally 500 female participants from five different institutions inurban and rural of Bangalore in 2020. Assessing baseline knowledge on breast cancer and BSE using selfadministeredquestionnaires as well as administering interventional health education in the form of a lecture,pamphlets and illustration of proper method of conducting breast self-examination using video tutorials.Conclusion: The baseline knowledge about breast cancer and BSE practice among participants for earlydetection was found to be insufficient. However, we witnessed a great progress after immediate and followup intervention. Periodic interventions are essential to prevent relapsing of certain types of barriers.